Pediatric research: laws and regulations - Hirschfeld, Steven (Henry Stewart Talks, 2025)
Evolution from protection to advocacy, Rationale for clinical studies in children, US and European pediatric initiatives, European Medicines Agency (Enpr-EMA), Pediatric ages